Silver/Polyethylene Glycol Nanocomposite Thin Films and its Biological Applications (JOURNAL OF ADVANCES IN CHEMISTRY, 2015)
The synthesis of silver nanoparticles with different sizes and concentrations was carried out using NaBH4 as a reducing agent and polyethylene glycol (PEG) as a stabilizer. The thin films of PEG embedded with Ag nanoparticles (Ag NPs) were deposited by electrospray deposition technique (ESD) and the morphology of subsequent prepared films was studied by AFM. Structure-property relationships of the colloid and subsequent films were discussed in dependence on the concentration of NaBH4. The synthesized Ag/PEG nanocomposite solution was characterized by UV-visible spectroscopy and Transmission electron microscopy (TEM). Chemical composition in the whole and on the surface of films were investigated by Fourier transform infrared (ATR-IR) and X-ray photoelectron microscopy (XPS), respectively. The UV-visible results indicate to the formation of spherical Ag NPs where the absorption peak was observed at wavelengths around 395 nm. TEM images showed the well dispersion of Ag NPs in the PEG matrix with average particle size of 13 nm.  Furthermore, the antimicrobial activity of the nanocmposite was studied. The Ag NPs released from the polymer matrix proven to have a significant antimicrobial activity against S. Pneumonia, B. Subtilis, E. Coli, and A. Fumigates.